Facile application of terahertz spectroscopy in UV-coated and phase change material loaded MPS - KAHRAMAN, MEMET VEZİR (My University, 2023)
In this study, capability of Terahertz (THz) spectroscopy for determination of thermal properties of phase change materials (PCM) in an acrylated polyurethane coating investigated. Spherical shaped mesoporous silica materials (MPSs) are prepared as a template for stearic acid (SA). SA was impregnated into MPSs for investigate its PCM properties. Surface of MPSs was modifed with 3-(Trimethoxysilyl)propyl methacrylate (MEMO) to add acrylate functionality to form covalently bond to polyurethane (PU)-based composite UV matrix to avert leakage problem. Finally, this resin was photopolymerized and its change in thermal properties was determined by both conventional Diferential Scanning Calorimetry (DSC) and THz. DSC results show that the heating process phase change enthalpy is measured between 20.83 J/g and 136.80 J/g, and the freezing process phase change enthalpy is found between 13.55 J/g and 181.13 J/g by DSC. The thermal properties of phase changing behavior of the sample were also analyzed by Terahertz Time Domain Spectroscopy (THz-TDS). Besides the phase changes THz spectroscopy has shown the temperature dependent variation in the host matrix, also fnal PCM sample. Comparison of the data suggest that THz Spectroscopy is a fairly strong technique for characterization of phase changing materials even in very complex resin environment and it is a strong complementary technique especially following the temperature dependent properties close to room temperature.
Keywords: Temel Bilimler; Mühendislik ve Teknoloji; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; Mesoporous material; Diferential scanning calorimetry (DSC); Terahertz spectroscopy; Photopolymerization; Phase change materials